CUSTOMS POLICY OF SOME LATIN AMERICAN COUNTRIES: FEATURES AND DEVELOPMENT - Атаманчук, Зорина (SWorldJournal, 2025)
The article examines the peculiarities of the customs policy of some Latin American countries, in particular, Argentina and Brazil. It is emphasized that integration processes in the region have led to the integration unions creation, which requires coord